(untitled) (Journal of Economic Research & Business Administration, 2016)
Focus on competition in the United States serves as a lever, stimulating companies to enhance innovation activity and renewal of industrial activity. The high level of competition has greatly contributed to the appearance of it in the US industrial parks, business incubators, venture funds, as well as the special economic zones of innovative type. The Japanese model of integration of science and industry, scientific and technological progress involves the construction of entirely new cities - tehnopolis focusing R & D and high-tech manufacturing. The Japanese government is funding approximately 25% of the total volume of R & D performed in the country. The main problems of innovative development of Kazakhstan are a lack of modern mechanisms for the implementation of technological innovation, a systematic approach to the management of innovation processes, developed infrastructure elements, the effective demand for advanced technology and industrial innovations.